PENGARUH CORPORATE GOVERNANCE TERHADAP MANAJEMEN LABA (Studi Pada Perusahaan Food and Baverages Yang Terdaftar di BEI - Pipit Rabiatun; Irianto Irianto; Indah Ariffianti; Baiq Kisnawati (Fakultas Ekonomi Universitas Islam Al-Azhar, 2020)
This study is aimed to examine the effect of corporate governance mechanisms, such as, independent board of. commissioner composition, board of commisioner size, audit committee, institutional ownership, and managerial ownership toward profit management. This research used 5 of food company and Baverages that was listed in Indonesia stock Exchange since 2014-2018. The sample of this research are selected by purposive sampling method. Analysis method of this research used multiple regression. Earnings management measured by using discretionary accrual. The result of this study showed that the result of regression as follow: = 7,365 + 0,631 XI + 0,553 X2 + 0,583 X3 + 0,674 X4 + 0,768 X5 + e. However the result of variable: (1) Composition of independent commissioner council has the effect of significant at profit management. It was proved by t value is higher than t table that was 4,291 > 2,085. (2) Standard of commissioner council has the effect of significant at profit management, it was proved by the result of t value is higher than t table that was 3,148 > 2,085. (3) the committee of audit has the effect of significant at profit management. It was proved by t value is higher than t value 3,569 > 2.085. (4) The ownership of constitutional has the effect of significant at profit management. It was proved by t value is higher than t table that was 4,422 > 2,085. (5) The ownership of managerial at profit management. It was proved by t value is higher than t table 5,618 > 2,085. (6) Composition of independent commissioner council, standard of commissioner council, the committee of audit, the ownership of constitutional, the ownership of managerial have the effect of significant at profit management. The result of calculation showed that f value that is 22,861, while f table 2,74 (22,861 > 2,74). It means that f value is higher than f table. The result of calculation of Composition of independent commissioner council, standard of commissioner council, the committee of audit, the ownership of constitutional, and the ownership of managerial showed that the value coofesien was 0,730 (73%) and the balance 0,270 (27%) it is described by other variable was not include in this research.